Actividad antimicrobiana in vitro de Naringina frente a patógenos de la cavidad oral. Revisión sistemática (2021)
Pathogenic and opportunistic microorganisms in the oral cavity microbiota cause localized and spreading infections in the body. Citrus fruit bioflavonoids such as naringin have several important properties, including antimicrobial properties. What is the research evidence for antimicrobial activity of naringin against main pathogenic bacteria in oral cavity?